Adoption of a Societal Perspective in Economic Evaluations of Musculoskeletal Disorders: A Conceptual Paper - Francis Fatoye; Tadesse Gebrye; Leo Nherera; Paul Trueman (Journal of Market Access & Health Policy, 2024)
Economic evaluations are used to compare the costs and consequences of healthcare interventions, including those for musculoskeletal (MSK) disorders, which are very common and a major source of morbidity and absence from work. Reimbursement decisions for interventions for MSK disorders by decision-makers rely on the findings of economic evaluations, the design and results of which depend largely on the perspective adopted. Despite methodological advancements in economic evaluations, there are no clear guidelines on the perspective to adopt. This paper explores the adoption of a societal perspective in economic evaluations of MSK disorders. Within health economics evaluations, the most commonly used perspectives include the payer perspective, the healthcare perspective, and the societal perspective. To facilitate optimal resource allocation decisions in order to reduce the significant economic burden of MSK disorders and improve the health outcomes of individuals with these disorders, all costs and benefits associated with interventions for them should be included. Thus, the societal perspective is arguably a preferable option to the others for economic evaluations of interventions for MSK disorders.